Strategi Pembelajaran Bahasa untuk Anak-Anak dengan Kebutuhan Khusus: Pendekatan Inklusif di Sekolah Dasar - Fenny Rahayu Muchlis; Chyntia Wongso Aidia; Lydia Natalia Amul (BADAN PENERBIT STIEPARI PRESS, 2021)
Objective: This research aims to explore effective language learning strategies for children with special needs in the context of inclusive education in elementary schools. The main focus of the research is to identify approaches that can improve the language skills of children with special needs and support their integration in regular classrooms. Method: This research uses qualitative methods with a case study approach. Data was collected through classroom observations, interviews with teachers and parents, as well as analysis of curriculum documents and learning materials. The research subjects consisted of five classes in an elementary school that implemented an inclusive approach, focusing on children with special needs. Results: Findings indicate that learning strategies involving the use of visual materials, assistive technology, and individualization approaches contribute significantly to improving the language skills of children with special needs. Active teacher involvement and parental support also play an important role in learning success. A well-designed, inclusive approach can reduce barriers to learning and facilitate better language development. Conclusion: An inclusive approach that applies learning strategies tailored to the individual needs of children with special needs has proven effective in improving their language skills. This research recommends implementing a variety of materials, using technology, and ongoing support from teachers and parents to create a more inclusive learning environment.